2004
DOI: 10.1515/ijmsp.2004.6.1-2.83
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Optimal Capacity Management in Reconfigurable Manufacturing Systems

Abstract: This paper presents an optimal policy, based on Markov decision theory for the capacity management problem in a firm facing stochastic market demand. The firm implements a reconfigurable manufacturing system and faces a delay between the times capacity changes are ordered and the times they are delivered. Optimal policies are presented as optimal boundaries representing the optimal capacity expansion and reduction levels. To increase the robustness of the optimal policy to unexpected events, the concept of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Control theoretic approaches base on a controller model (single-or double-loop) to dynamically control capacities of single work stations [18][19][20]. Up to now, approaches of reconfigurable manufacturing systems tend to remain on a rather abstract modelling level [21,22].…”
Section: Approaches Of Capacity Controlmentioning
confidence: 99%
“…Control theoretic approaches base on a controller model (single-or double-loop) to dynamically control capacities of single work stations [18][19][20]. Up to now, approaches of reconfigurable manufacturing systems tend to remain on a rather abstract modelling level [21,22].…”
Section: Approaches Of Capacity Controlmentioning
confidence: 99%
“…1. Distributions of the market demand [12] The capacity management dynamics evolves in discrete time. It is assumed that there is delay time from when the capacity is ordered until it can be utilized, shown by T. The dynamic capacity evolution is represented by: ) ; min(…”
Section: A Model Of Capacity Planning For Single Product Manufacturin...mentioning
confidence: 99%
“…2. Optimal Capacity Management Policy [12] Optimal thresholds levels L and U are obtained numerically by solving Equations (4). It is also shown that there exists optimal lower and upper limits for L and U shown by L*, and U* and the sufficient condition for a policy to be optimal is to be located within these two limits.…”
Section: A Model Of Capacity Planning For Single Product Manufacturin...mentioning
confidence: 99%
“…The optimal control theory based works by Asl and Ulsoy (2003), Matta et al (2007) develop an optimal policy where reconfiguration periods are considered in a single product with random demand environment. In the model proposed by Matta et al (2007), the ramp up is limited to a maximum of 50% of the available period.…”
Section: Literature Reviewmentioning
confidence: 99%